2023
DOI: 10.2478/forj-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

Importance and potential of Scots pine (Pinus sylvestris L.) in 21st century

Abstract: We are currently witnessing significant global changes in climate conditions. We cannot change the natural conditions, but with regard to sustainable landscape management, we can increase our knowledge of tree species and adapt forest management to them. Surprisingly, one of the most affected tree species in Central Europe today is Scots pine (Pinus sylvestris L.). The following literature review summarizes over 200 studies from 1952–2022 regarding Scots pine across its entire range while addressing various to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 146 publications
0
9
0
1
Order By: Relevance
“…Both species demonstrate notable resilience to drought, adaptability and production potential in the Central-European conditions [ 34 , 35 ]. As for Scots pine, despite some reported challenges linked to climate warming and nutrition [ 36 ], this species is expected to retain its current share as it often dominates on sandy soils and locations that would not be suitable for other tree species [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both species demonstrate notable resilience to drought, adaptability and production potential in the Central-European conditions [ 34 , 35 ]. As for Scots pine, despite some reported challenges linked to climate warming and nutrition [ 36 ], this species is expected to retain its current share as it often dominates on sandy soils and locations that would not be suitable for other tree species [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drought, in particular, has thus emerged as a determinant of radial growth and vigor of Scots pine and Norway spruce under conditions of advancing climate change (Augustaitis et al 2007;Bogino et al 2009;Putalová et al 2019;Brichta et al 2023). Moreover, trees damaged by browsing and bark stripping, which is very common in spruce compared to pine, suffer more from lack of precipitation and reduced growth (Cukor et al 2019a, b;.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has to be argued, whether all the current vitality problems resulting from pine's biology are considered reasonably in the silvicultural guidelines (Bose et al 2020;Rehschuh and Rühr 2021;Haberstroh et al 2022) and, when weighed, justify an increase cross-regionally. After all, economic and yield aspects play a central role in the discussion about the future cultivation suitability of coniferous tree species such as pine (Leuschner et al 2022;Brichta et al 2023). We also observed that the cultivation recommendation for pine is based on expert knowledge to this day and has not changed over time (Pfeil 1856;Wagenknecht 1955).…”
Section: Differences In Silvicultural Conceptsmentioning
confidence: 99%
“…Pure pine stands are particularly at risk in times of climate change which is mainly caused by drought, heat, insects, windthrow and fire (Hille 2006;Brandl et al 2020;Brichta et al 2023).…”
Section: Accelerating Flr Ratementioning
confidence: 99%
See 1 more Smart Citation